What is a good midwife? Some historical considerations - Borrelli, Sara E. (Royal College of Midwives, 2013)
AIM: This review takes into account some of the historical considerations around characteristics of a good midwife throughout the centuries in relation to historical and professional factors, tracing changing concepts from the definition of Soranus of Ephesus during the second century AD until the present day. METHOD: A structured literature search was undertaken to obtain information about the concept of the good midwife. Sources searched included historical textbooks, databases (Medline, ASSIA, Maternity and Infant Care, CINAHL) and reference lists. Data from a variety of European countries were considered and a range of primary and secondary sources in English language have been included. With regards to the contemporary literature, a selection of papers was reviewed in order to focus on the specific definition of what a good midwife is. This paper focuses on the historical aspects. FINDINGS: The contemporary concept of a good midwife seems to be mainly related to the combination of the following areas complementing each other: theoretical knowledge; clinical and professional competencies; communication skills; personal qualities; moral and ethical attitude. A connection between the past and present is apparent regarding what constitutes a good midwife with a focus on the competencies and qualities required of a midwife. The idea of good midwife in the past sometimes appears to place greater emphasis on physical characteristics and moral appraisal over theoretical knowledge, professional skills and practical experience. The idea of a ‘good midwife’ inevitably evolved in parallel within the social, cultural, economic, political and historical contexts. LIMITATIONS: This is not a systematic review and is subject to personal bias from interpretation. CONCLUSIONS AND IMPLICATIONS: There is no consensus on what factors are key to determining the qualities of a good midwife and there is continuous tension between the way in which the values associated with personal qualities, academic achievement and professional competencies are weighted. Professionals are encouraged to reflect on future challenges in providing good quality midwifery practice while working towards a more tangible identification of the fundamental characteristics of a good midwife.